Bithynien und Hellespont, Band 2 - Belke, Klaus (Verlag der Österreichischen Akademie der Wissenschaften, 2020)
The book contains detailed introductory chapters regarding the borders of the area in question, its history and church history, communications and economy in the Byzantine period. The body of the book consists of an alphabetical catalogue of all geographical names attested in written sources as well as of all settlements, fortresses, churches, monasteries etc. which are known only from archaeological remains.Band 1: https://e-book.fwf.ac.at/o:1436Band 2: https://e-book.fwf.ac.at/o:1437Große Karte: https://e-book.fwf.ac.at/o:1438Karte Konstantinopel Umgebung: https://e-book.fwf.ac.at/o:1439